2x-3y=8,4x+3y=-2

so 6x=6,so x=1,y=-2.

so 6x=6,so x=1,y=-2.

2x-3y=8,4x+3y=-2

so 6x=6,so x=1,y=-2.

so 6x=6,so x=1,y=-2.

X=1;y=-2 .

2x - 3y = 8 (1)

4x+3y=-2 (2),(1)+(2):2x - 3y +4x+3y=-2+8,6x=6,x=1,-3y=8-2,y=-2.

4x+3y=-2 (2),(1)+(2):2x - 3y +4x+3y=-2+8,6x=6,x=1,-3y=8-2,y=-2.

2x-3y=84x+3y=-2

Since 2x does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 2x from both sides.

-3y=-2x

Divide each term in the equation by -3.

-(3y)/(-3)=-(2x)/(-3)

Simplify the left-hand side of the equation by canceling the common factors.

Y=-(2x)/(-3)

Simplify the right-hand side of the equation by simplifying each term.

Y=(2x)/(3)

Since 2x does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 2x from both sides.

-3y=-2x

Divide each term in the equation by -3.

-(3y)/(-3)=-(2x)/(-3)

Simplify the left-hand side of the equation by canceling the common factors.

Y=-(2x)/(-3)

Simplify the right-hand side of the equation by simplifying each term.

Y=(2x)/(3)

Didn't find the answer you were looking for?